The effects of dexmedetomidine infusion on the formation of reactıve oxygen species during mesenterıc ischemia-reperfusion injury in rats - (:unkn) unknown (My University, 2007)
Amaç: bu çalışmanın amacı; sıçanlarda oluşturulan mezenter iskemi-reperfüzyon modelinde intravenöz uygulanan deksmedetomidinin reaktif oksijen ürün düzeyi üzerine etkilerinin araştırılmasıdır. Metod: 300-320 g ağırlığında, 28 adet, erkek, Spraque-Dawley cinsi sıçan dört gruba ayrıldı (n:7). Sham operasyonu geçiren iki gruptan; grup 1’deki sıçanlara (Kontrol grup, Grup K) ilaç uygulanmazken grup 2’deki sıçanlara 5 mg/kg/s deksmedetomidin infüzyonu yapıldı. Diğer iki gruba (grup 3 ve 4) süperior mezenter arter ligasyonu ile 30 dk iskemi ve ardından 60 dk reperfüzyon uygulandı (I/R). İskemi-reperfüzyon sırasında Grup 3’deki (I/R-S) sıçanlara 0.9% NaCl ve grup 4’deki (I/R-D) sıçanlara 5 mg/kg/h deksmedetomidin infüzyonu yapıldı. İleumdan, luminal ve lusigenin kemiluminesans (KL), doku miyeloperoksidaz aktivitesi, malondialdehid (MDA) ve glutatyon seviyesi ölçümleri için doku örnekleri alındı. Bulgular: Luminol KL seviyesi, doku miyeloperoksidaz aktivitesi (p<0.001) ve MDA seviyesi (p<0.05) I/R-S grubunda sham grupları ve I/R-D grubuna gore belrigin yüksek bulundu. Glutatyon seviyesi, I/R-S grubunda I/R-D grubundan belirgin yüksek bulundu (p<0.05). SONUÇ: Sıçanlarda intravenöz deksmedetomidin infüzyonunun mezenter iskemi-reperfüzyon modelinde oluşan reaktif oksijen türlerindeki artışı engellediği kanısına varılmıştır

Objective: The aim of this study was to evaluate the effect of dexmedetomidine infusion on the formation of reactive oxygen species during mesenteric ischemia-reperfusion injury in rats. Methods: Twenty-eight male Sprague-Dawley rats weighing between 300-320 g were divided into four groups (n=7). The first two groups underwent sham operation; group 1 was the control group and group 2 received 5 µg/kg/h dexmedetomidine iv infusion. Ischemia-reperfusion (I/R) was produced in the remaining two groups (group 3 and 4) by ligation of the superior mesenteric artery for 30 min followed by 60 min of reperfusion period. Group 3 (I/R-S) rats were control I/R rats receiving 0.9% NaCl infusion and group 4 (I/R-D) rats received 5 µg/kg/h dexmedetomidine iv infusion during I/R. Tissue samples were obtained from the ileum for the measurement of luminol and lucigenin enhanced chemiluminescence (CL), tissue myeloperoxidase activity, malondialdehyde (MDA) and glutathione levels. Results: Luminol CL levels, tissue myeloperoxidase activity (p<0.001) and MDA levels (p<0.05) were significantly higher in I/R-S group compared with sham-operated groups and I/R-D group. Glutathione levels of I/R-S group was significantly higher than those of I/R-D group (p<0.05). Conclusion: We concluded that dexmedetomidine infusion can prevent the increase in reactive oxygen species during mesenteric ischemia-reperfusion injury in rats.
Deksmedetomidin infüzyonunun sıçanlarda mezenter iskemi-reperfüzyon hasarında oluşan reaktif okisjen türleri üzerine etkisi
Keywords: Genel ve Dahili Tıp